Early stages in Ab1-42 spontaneous aggregation: an unbiased dataset from coarse-grained molecular dynamics simulations - Barrera Guisasola, Exequiel Ernesto (2024)
Soluble oligomers of Aβ-1-42 are widely recognized as crucial targets for the design of inhibitors for potential therapeutic intervention against Alzheimer´s disease. However, the intrinsically disordered character of this polypeptide poses serious difficulties for the experimental determination of conserved structural motifs. Indeed, initial aggregation steps are extremely challenging for state-of-the-art experimental techniques. Although molecular dynamics simulations harbor the potential to capture such initial association events, unbiased exploration of the conformational landscape available to unstructured dimers implies a significant computational cost. Here, we provide a dataset of configurations of Aβ1-42 dimers obtained by coarse-grained molecular dynamics (MD) simulations using the SIRAH force field. Trajectories are provided in standard gromacs format and can be easily converted to fully atomistic representations for visualization and analysis using molecular visualization/analysis software. The dataset contains MD trajectories of Aβ1-42 that undergo spontaneous and unbiased dimerization. We provide the time series of 25 replicates simulated for 10 microseconds under room conditions and physiological salt concentration. These multiple aggregation events provide valuable information not only on new binding pockets formed by the dimeric interface but also monomeric hot spots that can be targeted by small molecules on high-throughput docking campaigns. Alternatively, Aβ1-42 dimers could be used as aggregation seeds in studies of Aβ secondary nucleation